1996
DOI: 10.1021/ie960207u
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR Spectroscopy Study of the Polycarboxylic Acids Used for Paper Wet Strength Improvement

Abstract: Polycarboxylic acids have been used as cross-linking agents for cellulose to increase the wet strength of paper. In this research, we applied Fourier transform infrared (FT-IR) spectroscopy to study the kraft paper treated with poly(maleic acid) and 1,2,3,4-butanetetracarboxylic acid. FT-IR spectroscopy is used to measure the carboxyl of a polycarboxylic acid and ester on the treated paper. The ester carbonyl band intensity and the carbonyl band intensity ratio (ester/carboxylate) are used for the evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 9 publications
1
62
0
1
Order By: Relevance
“…This result indicates that Zn(NO 3 ) 2 is the most effective catalyst for the acetalization of glutaraldehyde by cellulose and PVA. For the purpose of comparison, NH 4 Cl is also included in the study. We find that NH 4 Cl provided a relatively constant W/D ratio around 30% in the pH range from 3.5 to 6.1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result indicates that Zn(NO 3 ) 2 is the most effective catalyst for the acetalization of glutaraldehyde by cellulose and PVA. For the purpose of comparison, NH 4 Cl is also included in the study. We find that NH 4 Cl provided a relatively constant W/D ratio around 30% in the pH range from 3.5 to 6.1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the purpose of comparison, NH 4 Cl is also included in the study. We find that NH 4 Cl provided a relatively constant W/D ratio around 30% in the pH range from 3.5 to 6.1 (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…24,25 It has been reported that the symmetric C¼O stretching band at high frequency is stronger than the asymmetric C¼O stretching band at low frequency for a noncyclic anhydride, and that the opposite is true for a cyclic anhydride. 25 In the present study, the peak intensity ratios of 1763 cm À1 /1801 cm À1 for Eudragit E and 1759 cm À1 /1799 cm À1 for the PVA copolymer were about 2.47 and 2.02, respectively. A high peak intensity ratio (41.0) implies that the cyclization due to intramolecular ester condensation was predominantly responsible for the cyclic anhydride formation occurring in the film of Eudragit E or PVA copolymer.…”
Section: Heat-induced Anhydride Formation In Eudragit or Pva Copolymementioning
confidence: 99%